Attainment of lipid goals and long-term mortality after coronary-artery bypass surgery. (March 2019) - Zafrir, Barak; Saliba, Walid; Jaffe, Ronen; Sliman, Hussein; Flugelman, Moshe Y; Sharoni, Erez
Introduction: There is paucity of data regarding lipid goal attainment after coronary-artery bypass graft surgery (CABG) and its impact on adverse outcomes. We aimed to investigate the attainment of lipid goals and the association between plasma lipid levels achieved after CABG and mortality. Methods: Retrospective analysis of 1230 patients undergoing CABG. Mortality was examined in relation to most-recent lipid levels attained, categorized by clinically-relevant thresholds, and according to the improvement from pre-operative levels. Results: Low-density lipoprotein cholesterol (LDL-C) < 70 mg/dL was attained by 44% of the patients. After multivariable adjustment, the hazard ratio for long-term mortality was 1.33 (95% confidence interval, 1.05–1.67) and 1.97 (1.55–2.50) for patients attaining LDL-C 70–100 mg/dL and >100 mg/dL, respectively, compared with LDL-C < 70 mg/dL. The hazard ratio was 1.42 (1.07–1.88) and 1.73 (1.33–2.23) for patients attaining high-density lipoprotein cholesterol (HDL-C) 40–50 mg/dL and <40 mg/dL, respectively, compared with HDL-C > 50 mg/dL; and 1.11 (0.85–1.45) and 4.28 (1.89–9.68) for patients with triglycerides 200–500 mg/dL and >500 mg/dL compared with triglycerides <200 mg/dL. A progressive stepwise association was seen between the cumulative status of the lipid measures achieved and long-term mortality, with the lowest risk observed in those with optimal level of all lipid measures ( p  < 0.0001). Improvement in any of the lipid measures from pre-operative to latest documented levels was associated with reduced mortality. Conclusions: Lack of attainment of optimal levels of routine lipid measures after CABG was common and associated both independently and additively with long-term mortality, emphasizing the importance of addressing plasma lipid profile as both a risk marker and a treatment target after CABG.